Assessment of antioxidant enzymes in response to exogenous titanium dioxide (TiO2) nanoparticles in Chainat 1 rice cultivar - Samart, Sutichai; Phakamas, Nittaya; Chutipaijit, Sutee (My University, 2018)
Antioxidant enzymes are important to prevent the destruction of photosynthetic pigments in plant cells. There have been reported that ZnO nanoparticles can promote activities of antioxidant enzymes in rice, but should not use in high activities because it can cause toxicity. Therefore, the objective of this study was to investigate the effect of titanium dioxide (TiO2) nanoparticles on the activities of antioxidant enzymes in Chainat 1 rice cultivar. Rice plants were treated with TiO2 nanoparticles using different concentrations i.e., 0, 100, 200, 400, 600 and 800 mg.L-1 for every 7 days-interval. Photosynthetic pigment contents (chlorophyll A, chlorophyll B and carotenoid) and activities of antioxidant enzymes (catalase and peroxidase) were recorded at 37, 44 and 51 days after planting. The results showed that the treatment of TiO2 nanoparticles was not effect on the quantities of chlorophyll A, chlorophyll B and carotenoids, but found that the activities of peroxidase and catalase enzymes were significant affected at all growth stages. Especially, at a concentration of 200 mg.L-1 TiO2 found that rice plants contained the highest activities of peroxidase enzyme and significant difference from control treatment. However, the treatments of higher dose than 200 mg.L-1 TiO2 would have a chance to meet toxicity in rice plants as the activities of antioxidant enzymes were decreased.
Keywords: Antioxidant enzymes; Photosynthetic pigments; Rice; TiO2 nanoparticles